Community-Driven Textile Recycling for Sustainable Livelihoods: A Case Study of the Padat Karya Tunai Program in Kragan Village, East Java - Febriani, Maya; Haque, Ziyaul (Bisma : Bimbingan Swadaya Masyarakat, 2024)
The Padat Karya Tunai (PKT) program in Kragan Village, East Java, utilized waste fabric as a resource to create economically valuable products, such as masks, while promoting environmental sustainability and community empowerment. This study, based on the Participatory Action Research (PAR) methodology, explores the program's impact on economic and social outcomes within a rural community. 50 local participants, primarily women, were trained in textile recycling and entrepreneurship. Over six months, participants produced over 5,000 masks, resulting in a 20-30% increase in household income. Additionally, 2,000 kg of textile waste was recycled, contributing to a reduction in environmental pollution. The findings indicate that the PKT program successfully addressed immediate economic needs and fostered social inclusion, particularly for women. However, challenges related to the temporary nature of employment, market access, and resource availability remain, limiting the program’s long-term sustainability. This study recommends incorporating vocational training, microfinance, and local partnerships to ensure the program's continued impact and scalability in other rural communities.